Behaviour in a business context - Turton, Richard. (Chapman and Hall, 1991)
Introduction. The origins of the modern work organization. The factory system of work and behaviour. The role and structure of organizations. Strategic choice and the basis of power in organizations. Information and decisions in organizations. The individual and behaviour at work. Organizational structures and strategies for the future. Organization structure. International comparisons.